A security optical tree establishment protocol based on distributed path computation element in multi-domain optical networks - Zhou, Yang; Wu, Qiwu; Jiang, Lingzhi (Journal of physics. Conference series, 2020)
How to build a secure optical tree through signalling mechanism in multi domain optical network is an important problem. To solve the problem, a security optical tree establishment protocol based on distributed Path Computation Element (PCE) in multi-domain optical networks was proposed. The protocol used a distributed PCE architecture. By expanding the optical network control plane and integrating multiple security mechanisms, the new signaling process of establishing a multicast optical tree was designed. The analysis and experimental results showed that, the protocol performed better performance in a malicious environment compared with the typical layered PCE-based protocol.